Unravelling the ketone story. Secondary vessel use at the Ness of Brodgar, Orkney, Scotland - Julia Becher; Alexandre Lucquin; Rowan McLaughlin; Martine Regert; Mark Edmonds; Jan Blatchford; Nick Card; Anne Mitchell; Helen M. Talbot; Roy Towers; Oliver E. Craig (Organic Geochemistry, 2026)

Organic geochemical investigations of an MIS 5 fire in the Palaeolithic deposits of Ormesson (Seine-et-Marne, France): Anthropic or natural? - Ivy Notterpek; Alexandre Lucquin; Samuel Abiven; Pierre Bodu; Tobias Bromm; Bruno Glaser; Henri-Georges Naton; Matthew D. Pickering; Oliver E. Craig; Isabelle Théry-Parisot (Quaternary Science Reviews, 2026)

Culinary continuity in central Japan across the transition to agriculture - Jasmine Lundy; Manon Bondetti; Alexandre Lucquin; Helen M. Talbot; Natsuki Murakami; Seiji Nakayama; Motoki Harada; Miho Suzuki; Eiko Endo; Chris Stevens; Enrico R. Crema; Oliver E. Craig; et al. (Archaeological and Anthropological Sciences, 2024)
Rice and millet arrived in Western Japan from Korea around 3,000 years ago and spread eastwards across the archipelago in the next 700 years. However, the extent to which agriculture transformed traditional Jōmon hunter-gatherer-fisher communities is debated. Central Japan is a key area of study as remodelling of radiocarbon dates shows a slowdown in the dispersal rate of rice agriculture in this area. Here, we examine and compare the use of pottery by Final Jōmon and Early to Middle Yayoi communities in the Tōkai and the Central Highland regions of central Japan, using lipid residue analysis. Although the identification of specific biomarkers for rice remains elusive, an increase in the ratio of E/H C 18 APAAs with the arrival of rice and millet indicates a potential change in plant processing and consumption. We were also able to identify biomarkers for broomcorn millet (miliacin) in both Final Jōmon and Yayoi pottery. However, evidence for millet consumption is sparse and in all cases was likely mixed with wild hunted and foraged foods. We conclude therefore that, despite the introduction of rice and millet agriculture in central Japan, pre-existing diets and culinary habits of Jōmon hunter-gatherers remain important.

An experimental study of wet-cooking in organic vessels: implications for understanding the evolution of cooking technologies - Andy Langley; Andy Needham; Roland Kröger; Gabriel Cifuentes-Alcobendas; Mette Adegeest; Jess Cousen; Christopher Lance; Hannah Benton; Amy-Rose Mansbridge; Amanda Satchell; Lewis Tomlinson; Francesca Rockall-Birtles; et al. (Archaeological and Anthropological Sciences, 2023)
The ability to control and direct fire is a major evolutionary step in the human story. The development of aceramic cooking technologies is less well understood as they rarely survive in the archaeological record. However, inferential evidence such as fire-cracked rocks, earthen pits and heated bones suggest a variety of cooking methods were used prior to the invention of ceramics. Yet there is a paucity of experimental evidence testing the efficacy of perishable organic containers in tasks involving their use with heat. The study presents experimental results of organic containers and their use for heating water related to cooking. Containers were made from deer hide and pig stomach and water was heated using two different techniques: placing the container directly above a fire and placing hot stones into the container. The results suggest that different organic containers and heating types could attain and maintain a sub-boiling cooking temperature; however, not all could reach boiling point. It is argued that these sub-boiling methods may be as, or perhaps more, desirable than boiling, with potential implications for the development of vessels prior to the adoption of ceramics.

Molecular evidence for new foodways in the early colonial Caribbean: organic residue analysis at Isla de Mona, Puerto Rico - Lisa Briggs; Jago Cooper; Oliver E. Craig; Carl Heron; Alexandre Lucquin; María Mercedes Martínez Milantchi; Alice Samson (Archaeological and Anthropological Sciences, 2023)
Ceramic objects account for over 90% of the cultural material recovered from archaeological sites in the Caribbean. However, little research has been conducted on molecular evidence for past food production from these same vessels. Forty ceramic sherds from Isla de Mona have been analysed by GC–MS and GC-C-IRMS in order to address questions surrounding foodways in the Greater Antilles prior to and post European arrival. We evaluate evidence for dietary changes to illuminate aspects of cultural exchange between Indigenous populations and the first generations of Spanish colonists. Here, we show that plant residues are found in a variety of pottery forms, with some evidence for non-ruminant and ruminant fats. The dearth of marine biomarkers is curious given the volume of fish bones found in archaeological contexts on Isla de Mona and may offer evidence for spit-roasting, pit-roasting, or the use of a ‘barbacoa’ to cook fish on the island. The ubiquity of plant residues in a variety of pottery forms may relate to the large-scale cultivation and export of cassava ( Manihot esculenta ) from the island. A Spanish olive jar revealed evidence of wine residues, which may constitute the earliest detection of wine residues in pottery found in the Americas.

Neolithic farmers or Neolithic foragers? Organic residue analysis of early pottery from Rakushechny Yar on the Lower Don (Russia) - Manon Bondetti; Lara González Carretero; Ekaterina Dolbunova; Krista McGrath; Sam Presslee; Alexandre Lucquin; Viktor Tsybriy; Andrey Mazurkevich; Andrey Tsybriy; Peter Jordan; Carl Heron; John Meadows; et al. (Archaeological and Anthropological Sciences, 2021)
The emergence of pottery in Europe is associated with two distinct traditions: hunter-gatherers in the east of the continent during the early 6th millennium BC and early agricultural communities in the south-west in the late 7th millennium BC. Here we investigate the function of pottery from the site of Rakushechny Yar, located at the Southern fringe of Eastern Europe, in this putative contact zone between these two economic ‘worlds’. To investigate, organic residue analysis was conducted on 120 samples from the Early Neolithic phase (ca. mid-6 th millennium BC) along with microscopic and SEM analysis of associated foodcrusts. The results showed that the earliest phase of pottery use was predominantly used to process riverine resources. Many of the vessels have molecular and isotopic characteristics consistent with migratory fish, such as sturgeon, confirmed by the identification of sturgeon bony structures embedded in the charred surface deposits. There was no evidence of dairy products in any of the vessels, despite the fact these have been routinely identified in coeval sites to the south. Further analysis of some of the mammalian bones using ZooMS failed to demonstrate that domesticated animals were present in the Early Neolithic. Nevertheless, we argue that intensive exploitation of seasonally migratory fish, accompanied by large-scale pottery production, created storable surpluses that led to similar socio-economic outcomes as documented in early agricultural societies.

First lipid residue analysis of Early Neolithic pottery from Swifterbant (the Netherlands, ca. 4300–4000 BC) - Özge Demirci; Alexandre Lucquin; Oliver E. Craig; Daan C.M. Raemaekers (Archaeological and Anthropological Sciences, 2020)
This paper focuses on the functional analysis of Swifterbant pottery from North-western Europe (ca. 4300–4000 BC) through lipid residue analysis. The main aim is to understand the role of pottery in terms of its relation to hunter-fisher-gatherer lifestyle, and the change in available food resources brought about by the arrival of domesticated animal and plant products. We conducted lipid residue analysis of 62 samples from three Swifterbant sites S2, S3 and S4. A combined approach using both GC-MS and GC-C-IRMS of residues absorbed into the ceramic was employed to identify their context. Our results demonstrate that Swifterbant ceramics were used exclusively for processing aquatic resources. We also found no evidence of inter-site variation in the use of pottery or variation based on both typological and technological features of the pottery. We found no evidence for any domesticated resources despite their presence in the faunal and botanical assemblages.

Diet, cuisine and consumption practices of the first farmers in the southeastern Baltic - Harry K. Robson; Raminta Skipitytė; Giedrė Piličiauskienė; Alexandre Lucquin; Carl Heron; Oliver E. Craig; Gytis Piličiauskas (Archaeological and Anthropological Sciences, 2019)

Long-term dietary change in Atlantic and Mediterranean Iberia with the introduction of agriculture: a stable isotope perspective - Miriam Cubas; Rita Peyroteo-Stjerna; Maria Fontanals-Coll; Laura Llorente-Rodríguez; Alexandre Lucquin; Oliver Edward Craig; André Carlo Colonese (Archaeological and Anthropological Sciences, 2019)